Correlation between varus-type knee osteoarthritis severity and hindfoot alignment: Analysis of radiographs in the long-leg weight-bearing anteroposterior view - Yusuke Ozaki; Ryota Hara; Kensuke Okamura; Hiroaki Kurokawa; Yusuke Inagaki; Munehiro Ogawa; Akira Taniguchi; Yasuhito Tanaka (PLoS ONE, 2025)
Background In knee osteoarthritis, the subtalar joint undergoes valgus and varus contractions to compensate for deformities in the knee joint. In this cross-sectional study, we investigated the relationship between varus-type knee osteoarthritis severity and hindfoot alignment severity by concurrently assessing varus-type knee osteoarthritis severity and hindfoot alignment using radiographs in the long-leg weight-bearing anteroposterior view. Patients and methods A total of 114 patients with knee osteoarthritis graded Kellgren–Lawrence II or higher (128 knees) and 30 healthy controls (31 knees) underwent long-leg weight-bearing anteroposterior imaging for 1 year. Four angles were measured on radiographs in the long-leg weight-bearing anteroposterior view: the femorotibial angle; tibial calcaneal angle; tibial anterior surface angle; and talocrural joint angle between the tibial plafond and talar dome on weight-bearing. Group comparisons were conducted for each Kellgren–Lawrence classification, which was used to classify the severity of knee osteoarthritis at each measured angle. One-way analysis of variance was used to test the results. Results The mean tibial calcaneal angles were 9.7°, 11.3°, 8.8°, and 9.8° in controls and in patients with Kellgren–Lawrence grades II, III, and IV, respectively (p < 0.05). The mean femorotibial angles were 175.6°, 176.8°, 180.3°, and 186.2° in controls and in patients with Kellgren–Lawrence grades II, III, and IV, respectively (p < 0.05). On weight-bearing, the tibial anterior surface angle and the talocrural joint angle between the tibial plafond and talar dome varied according to severity level. Conclusion In varus-type knee osteoarthritis cases, defined in accordance with the Kellgren–Lawrence classification, hindfoot alignment leaned toward valgus. As the severity of knee osteoarthritis progressed, the valgus of the hindfoot alignment reduced. While future longitudinal analyses are necessary, these observations indicate both potential compensatory changes and their limitations in varus-type knee osteoarthritis.